How Human and Organizational Factors Influence Software Teams Productivity in COVID-19 Pandemic: A Brazilian Survey - Bezerra, Carla I. M.; Filho, José Cezar de Souza; Coutinho, Emanuel F.; Gama, Alice; Ferreira, Ana Lívia; Andrade, Gabriel Leitão de; Feitosa, Carlos Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Software companies have adopted remote work to maintain practitioners safe during the COVID-19 outbreak worldwide. The remote environment in pandemic time brings some challenges, mainly for practitioners with limited experience with this work modality. Moreover, there are several factors in the environment that together with the change in the work routine can directly impact the teams productivity, such as human and organizational factors. To investigate this problem, we conducted a survey applied to software teams in Brazil to analyze how such factors can influence their productivity in the remote environment during the COVID-19 pandemic. The survey was guided by human and organizational factors identified in the literature that affect the productivity of software teams, such as: work environment, collaboration and organization of teams, communication, motivation, among others. Our survey obtained 58 participants from all Brazilian regions. As main conclusions, we identified that 74.1% of the participants consider their productivity remains good or excellent, and 84.5% feel motivated and have easy communication with their co-workers. Furthermore, the main factors influencing the productivity are external interruption, environment adaptation, and emotional issues.